Analisis Pengelolaan Modal Kerja terhadap Kinerja Keuangan pada Perusahaan Daerah Air Minum (PDAM) Tirta Musi Palembang - Rauly Sundate; Asmanita, Asmanita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Working capital is the excess of current assets over short-term debt. This excess is called net working capital. This excess is the amount of current assets that come from long-term debt and own capital. Ratio analysis is an analysis carried out by connecting various estimates in financial reports in the form of financial ratios. This financial ratio analysis can reveal important relationships between financial report estimates and can be used to evaluate the company's financial condition and performance. This research aims to determine the analysis of working capital management at PDAM Tirta Musi. To find out the Company's Financial Performance at PDAM Tirta Musi. To find out the Working Capital Analysis of Company Financial Performance at PDAM Tirta Musi Palembang. To obtain the necessary data and information, the author conducted research on PDAM Tirta Musi Palembang. From the results of the research that has been carried out, the results show that the profitability ratio using ROA (Return On Assets) calculations shows that the performance of the PDAM Tirta Musi Palembang Company is in good condition.